Performance and cost of a renal cancer specialist multidisciplinary team meeting: Results from 1500 discussions. (July 2019) - Neves, Joana B; Shepherd, Scott; Cullen, David; Powles, Tom; Aitchison, Michael; Tran, Maxine G B
Objectives: To report on the performance and cost of a surgeon-led renal cancer specialist multidisciplinary team meeting at a high-volume centre. Materials and methods: Retrospective analysis of 1500 consecutive cases discussed from 2 September 2015 onwards. Performance was assessed as the number of cases where a clinical recommendation was made. The cost per meeting, discussion and patient were calculated using the mid-point of pay band attributable to the attendees (National Health Service pay scales 2015). Results: Over 34 meetings, 1500 discussions occurred (933 patients: 61.7% male; mean age 63.8). Above a one-quarter of discussions ( n = 399, 26.6%) were new referrals. Each patient's case was discussed a mean of 1.6 times, the majority being discussed once ( n = 563, 60.3%). In 93.3% of discussions, a clinical recommendation was made. Only 100 discussions (6.7%) were deferred due to incomplete clinical information. A total of 11.1% ( n = 166) cases were discharged. The average costs were: £141, 901 per year, £2729 per meeting, £62 per case discussed and £99 per patient. Conclusion: One discussion was usually sufficient to decide management; deferral was uncommon; and, given the low discharge rate, referrals seemed appropriate. The cost per patient was modest, and represented good value in providing a focused and shared clinical decision-making pathway for renal cancer patients. Level of evidence: 2C